Throughput Accounting and its role in supporting and achieve competitive advantage - الحمداني بهاء حسين; خلف عامر دحام (Journal of Economics and Administrative Sciences, 2016)
Abstract Dealing economic units at the present time with an industrial environment characterized by competitiveness and the pace of change and its strength as a result of this changing environment shall be on those who made it to adopt strategies that allow them to confront these variables and work in order to meet the market requirements of quality and price appropriate products to suit and the demand for those products and conditions to maintain its competitive position and its development. As a result, it became the subject of competitiveness in recent years and enjoys widespread attention at the global level. And in order to keep up with the great development witnessed by the world and of the phenomenon of globalization and integration into the global economy and the policies of opening up and liberalization of markets in addition to the tremendous developments in information and communication technology requirements. So it come under systems of traditional cost accounting for many of the criticisms that revolve around the inadequacy of these systems developments and transformations taking place in the modern industrial environment and the consequent need to make fundamental changes in the costs of systems management and accounting in order to fit the competitive environment in order to support the economic capacity and improve production efficiency. In response to all this it emerged the concept of accountability for achievement and who tried to provide a new concept of cost and different from the traditional concept of a standards development related thereto and to try to introduce new concepts are simple and easily reached is viewed as the cost of raw materials only variable element and deal wages as a single fixed cost elements.